THE AUDIT QUALITY BATTLEGROUND: AI, PROFESSIONAL SKEPTICISM, EXPECTATION GAPS, AND AUDIT PROCESS EFFECTIVENESS FIGHTING FOR DOMINANCE IN MALAYSIA’S PUBLIC ACCOUNTING FIRMS - Hazlin, Aida (JEA17: Jurnal Ekonomi Akuntansi, 2025)
The increasing complexity of financial management in government organizations has heightened the risk of fraud, making effective prevention mechanisms a critical priority. The digitalization of accounting systems is considered a strategic approach to enhancing transparency, accuracy, and real-time monitoring of financial transactions. This study aims to examine the effect of accounting system digitalization on fraud prevention in government organizations, with internal control functioning as a moderating variable. This research employs a quantitative approach using a survey method. Data were collected from government employees involved in accounting and financial reporting processes. The analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS application. The measurement model (outer model) was evaluated through convergent validity, discriminant validity, and reliability tests, while the structural model (inner model) was assessed using path coefficients, coefficient of determination (R²), and predictive relevance (Q²). The results indicate that the digitalization of accounting systems has a positive and significant effect on fraud prevention. Furthermore, internal control significantly moderates the relationship between accounting system digitalization and fraud prevention, strengthening the effectiveness of digital systems in reducing fraud risk. The model demonstrates adequate explanatory power, as reflected by satisfactory R², SRMR, and Q² values. These findings suggest that the successful implementation of accounting system digitalization, supported by strong internal control mechanisms, can significantly enhance fraud prevention efforts in government organizations. This study contributes to the literature on public sector accounting and provides practical implications for policymakers in designing effective digital governance and anti-fraud strategies.